PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA GURU - yanto, supri (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2014)
Abstract: The objectives of this research are to investigate: (1) whether or not of the motivation on the teacher job satisfaction in SMK PGRI Sukoharjo year 2012/2013; (2) whether or not of the work environment on the teacher job satisfaction in SMK PGRI Sukoharjo year 2012/2013; and (3) whether or not the simultaneusly effect of the effect motivaton and the work environment on the teacher job satisfaction in SMK PGRI Sukoharjo year 2012/2013. This research used the descriptive quantitative research method. The population of the research was all of the teacher SMK PGRI Sukoharjo year 2012/2013 as many as 58 teachers. The sample of the research consisted of 35 teachers or 60% out of the total number of population, and they were taken by using random sampling technique. The data of the research were gathered by using questionnaire and documentation. They were then analyzed by using the multipel linear regression technique of analysis.The results of the research are as follows: (1) there is a significant of the motivation on the teacher job satisfaction in SMK PGRI Sukoharjo year 2012/2013; (2) there is a significant of the work environment on the teacher job satisfaction in SMK PGRI Sukoharjo year 2012/2013; and (3) there is a simutaneusly significant of the motivation and that of the work environment on the teacher job satisfaction in SMK PGRI Sukoharjo year 2012/2013.The linear regression line equation is ?= -10,014 + 0,546X1 + 0,413X2. The relative contribution of the motivation on the teacher job satisfaction in SMK PGRI Sukoharjo year 2012/2013 is 58.33%, and that of the work environment on the teacher job satisfaction in SMK PGRI Sukoharjo year 2012/2013 is 41.67%. The effective contribution of the motivation on the teacher job satisfaction in SMK PGRI Sukoharjo year 2012/2013 is 23.26%, and that of the work environment on the teacher job satisfaction in SMK PGRI Sukoharjo year 2021/2013 is 16.62%.Suggestion to head master that more attention teacher prosperious, suggestion to teacher that take care work environment office or class, for school comite that to gain up work environment. Keywords: motivation, work environment, job satisfaction of teachers